Peningkatan Pemahaman Pancasila Sebagai Ideologi Negara Dan Identitas Nasional Kepada Siswa Tentang Pendidikan Anti Korupsi - Marwenny, Elwidarifa; Firsta, Firsta; Hastini, Lasti Yossi; Mariyanti, Eka; Valentina K, Yunita; Yufiandra, Defika; Raihan, Raihan; Hardianto, Irvan; Istifara, Dinda Rahmi; Mawwaddah, Aulia; Firdaus, Kevin Yuhedi; Putri, Tifanny Syentia; Rahmadani, Dwi; Estasia, Sepriani; Rizki Zulmi, Cahaya Adinda; Fakhriano, Silvi; Situmorang, Al Hafiz (LPPM Universitas Dharma Andalas, 2025)
Corruption is one of the greatest threats to the development and prosperity of the Indonesian nation. This phenomenon not only harms the country's economy but also destroys public morals and trust. Efforts to eradicate corruption require a comprehensive approach that encompasses education from an early age. Anti-corruption education, particularly at the elementary school level, is a crucial strategy for instilling the values of integrity and honesty as the character building blocks for future generations. This community service activity aims to increase elementary school students' understanding of anti-corruption values, grounded in Pancasila as the state ideology and Pancasila as the National Identity. Interactive training methods involving discussions, questions and answers, and simple games were used to encourage student participation in understanding the harmful impacts of corruption and the importance of integrity. The program results showed that 90% of participants understood the material presented, emphasizing the importance of character education as a foundation for creating a young generation with integrity and the ability to resist corruption. With positive results, it is hoped that similar programs can be implemented in other regions to expand their impact significantly on society.